ANALISIS PENGGUNAAN BAHASA PROKEM DALAM NOVEL REACH YOUR DREAMS KARYA WIRDA MANSUR - Nur Fazriah Maulani; Teti Sobari; Sary Sukawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is motivated by the fact that slang language is slang, although the style is deviant or includes slank language but is commonly used by teenagers. One of them is in the novel Reach Your Dreams by Wirda Mansur, which features slang in order to suit the target audience of teenagers. The purpose of this research is to; 1) Identify the slogan contained in the novel Reach Your Dreams by Wirda Mansur, and 2) describe the results of language analysis from the aspects of language (phonology, morphology and semantics). This study used descriptive qualitative method. The data in this study are words in the form of slang, obtained from the novel Reach Your Dreams by Wirda Mansur. The data was collected using the basic techniques of reading and taking notes, namely the analysis instrument in the form of a study of research results. The results showed that; 1) in the novel Reach Your Dreams by Wirda Mansur, there are around 90 slang words, and 2) the phonological aspect is 31,11%, the morphological aspect is 14.45%, and the semantic aspect is 54.44%. The slang language used is in the form of abbreviations, acronyms, conversational language which is converted into written form, foreign languages, and words that are not in accordance with the provisions. The use of slang in the novel makes the novel more fluid and acceptable to teenage readers.